Project portfolio selection in a colombian holding company - Rincón, Camilo Andrés Micán (2018)
The adequate project selection allows companies to invest resources in specific initiatives that allow them to achieve their strategic objectives and to become more competitive. In contrast, non-adequate projects selection can burden the organizations with large investments that do not impact positively in the organization in general. This paper shows an application of Promethee I method, fifth version, as a multi-criteria method to support the strategic projects selection process, and a sensitivity analysis that were both carried out at the beginning of the planning period in a Colombian holding company. The application of Promethee I in a base scenario, and the development of two alternative scenarios allowed to identify that in the case study’s portfolio there are projects with a very high preference, regardless of the criteria weight. Similarly, it allowed to identify the least preferred projects. These results are an important input for projects selection decision-making to be carried out by the holding company board of directors. Moreover, it was identified that the case study’s holding company should focus efforts on the relative weights definition and on the measurement scale of each criterion, as this has a significant impact on the results obtained.